Gold(i)–silver(i)-calix[8]arene complexes, precursors of bimetallic alloyed Au–Ag nanoparticles. Issue 7 (14th May 2020) - Clément, Marie; Abdellah, Ibrahim; Martini, Cyril; Fossard, Frédéric; Dragoe, Diana; Remita, Hynd; Huc, Vincent; Lampre, Isabelle
Abstract : We report the synthesis of new bimetallic gold(i )–silver(i ) calix[8]arene complexes and their radiolytic reduction leading to small Au–Ag alloyed nanoparticles. Abstract : In this paper, we report the first synthesis and characterisations of bimetallic gold(i )–silver(i ) calix[8]arene complexes. We show that the radiolytic reduction of these complexes leads to the formation of small bimetallic nanoparticles with an alloyed structure, as evidenced by XPS, HR-TEM and STEM/HAADF-EDX measurements.